Etos dagang orang jawa : pengalaman Raja Mangkunegara IV - Daryono, 1961- (Yogyakarta : Pustaka Pelajar, 2007)
Javanese ethics on trade and business of Mangkunegara IV.
Originally presented as the author's thesis (M.S.I--Institut Agama Islam Negeri Walisongo, 2007) under title: Etos dagang Jawa, studi terhadap pemikiran Sri Mangkunegara IV.
Includes bibliographical references (p. 316-328).
Keywords: Javanese (Indonesian people) -- History; Javanese (Indonesian people) -- Social life and customs